The Public Work: Redefining the Standard for an Urban Society - Timothy de Noble (Oz, 2012)
A common lament of our era is that our cities are undefined, usually in reference to the lack of an easily circumscribed boundary. The once defined, bounded, defensible city is committed to history, undone by modern weaponry, howitzers, bombers, automobiles and their highways, and the interconnectivity of cyberspace.